2019
DOI: 10.4103/ijem.ijem_623_18
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of diabetes using the Indian diabetes risk score: A study on young medical students from Northern India

Abstract: Context: Identification of risk factors of diabetes is required among youth as diabetes in young persons is now spreading in epidemic proportions. Indian Diabetes Risk Score (IDRS) is a validated and cost- effective tool to identify risk of diabetes among population. Aims: Present study was conducted among young medical students to assess risk of type 2 diabetes mellitus (T2DM) using the IDRS and to study association of risk of diabetes with other factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
(6 reference statements)
5
8
0
Order By: Relevance
“…While 68% of the students reported a family history of diabetes mellitus, the current findings were lower than those of a study conducted among medical students in India [17] and found a high risk in 5% and a moderate risk in 55%. Another study from India [18] found that 23% of the students were in the high-moderate category, in similarity to the current findings. A family history of diabetes was found in 25% of the Indian medical students and is lower than the current findings in which 62% of the medical students reported a family history of diabetes mellitus.…”
Section: Discussionsupporting
confidence: 90%
“…While 68% of the students reported a family history of diabetes mellitus, the current findings were lower than those of a study conducted among medical students in India [17] and found a high risk in 5% and a moderate risk in 55%. Another study from India [18] found that 23% of the students were in the high-moderate category, in similarity to the current findings. A family history of diabetes was found in 25% of the Indian medical students and is lower than the current findings in which 62% of the medical students reported a family history of diabetes mellitus.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the multivariable analysis are consistent with earlier research that showed gender discrepancies in metabolic health and emphasizes the significance of taking gender into account when measuring IDRS [ 23 ]. Furthermore, another study conducted among undergraduate students from north India also supported the fact that males are at a higher risk [ 24 ]. Studies also support the documented link between tobacco use and harmful metabolic consequences at a very early age [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 89%
“…11 Singh et al found that risk of developing diabetes was high in 6% subjects, moderate in 44.3% and low in 49.7% participants. 12 This could be attributed to the difference in the study population between various studies. There is also variation in the distribution of the age, socio-demographic profile and geographical distribution of the study population.…”
Section: Discussionmentioning
confidence: 99%